A Real-Time Restraint Method for Range Walk Error in 3-D Imaging Lidar Via Dual Detection - Ling Ye; Guohua Gu; Weiji He; Huidong Dai; Qian Chen (IEEE Photonics Journal, 2018)
Geiger-mode avalanche photodiode (Gm-APD) offers 3D imaging lidar much better capability in terms of detection sensitivity. However, a range walk error (RWE) exists in Gm-APDs which refers to the fluctuation of the measured distance as a function of the intensity of echo pulses. In this paper, we present a real-time restraint method for RWE implemented by unequally intensity-dividing the echo pulses into two Gm-APDs. The difference image of two depth images measured by the divided beams is a matrix of RWE distribution and the intensity image is used to censor the anomalous pixels in the matrix. Combined with the matrix of RWE distribution, an accurate depth image with low RWE can be obtained. Experimental results demonstrate that the proposed method reduces approximately 86% RWE of the conventional method in real time.